2018
DOI: 10.1016/j.cortex.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

When attended and conscious perception deactivates fronto-parietal regions

Abstract: The finding of increased fronto-parietal activity during conscious and attended perception forms a key basis for theories of consciousness and attention. However, this finding comes largely from studies that required explicit detection of events in a way that made detection the goal of the ongoing task. This is an important confound because goal completion itself elicits fronto-parietal activity. In everyday life attended and conscious perception is instrumental in achieving our goals but rarely a goal in itse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…Thus, even though neural activity associated with perceiving a task-relevant stimulus (report condition) versus a task-irrelevant stimulus (no-report condition) could be compared, we were unable to make the critical contrast between perceived versus not-perceived stimuli. This same limitation applies to two recent functional magnetic resonance imaging experiments that attempted to test the contribution of frontal cortical areas to conscious perception [110,115]. Farooqui & Manly [115] reported deactivations of frontal cortical areas for non-target stimuli that were clearly seen.…”
Section: Conscious Perception Of Task-irrelevant Stimuli: Design Detamentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, even though neural activity associated with perceiving a task-relevant stimulus (report condition) versus a task-irrelevant stimulus (no-report condition) could be compared, we were unable to make the critical contrast between perceived versus not-perceived stimuli. This same limitation applies to two recent functional magnetic resonance imaging experiments that attempted to test the contribution of frontal cortical areas to conscious perception [110,115]. Farooqui & Manly [115] reported deactivations of frontal cortical areas for non-target stimuli that were clearly seen.…”
Section: Conscious Perception Of Task-irrelevant Stimuli: Design Detamentioning
confidence: 96%
“…This same limitation applies to two recent functional magnetic resonance imaging experiments that attempted to test the contribution of frontal cortical areas to conscious perception [110,115]. Farooqui & Manly [115] reported deactivations of frontal cortical areas for non-target stimuli that were clearly seen. Wiegand et al [110] showed that some (but not all) of the frontal activity observed in a perceived versus nonperceived contrast for task-relevant stimuli disappeared during a separate experiment when the same stimuli were always perceived, but were irrelevant to the task.…”
Section: Conscious Perception Of Task-irrelevant Stimuli: Design Detamentioning
confidence: 96%
“…2. Target detection is the explicit behavioural goal of the task and therefore, detected targets have higher behavioural relevance than undetected targets (Farooqui and Manly, 2018). 3.…”
Section: Introductionmentioning
confidence: 99%
“…We dissociate corresponding representations in the brain by means of Bayesian Model Selection (BMS, Stephan, Penny, Daunizeau, Moran, & Friston, 2009), which determines which model best explains the data in every voxel of the brain based on model evidence maps. Building on insights from the visual modality (Farooqui and Manly, 2018; Frässle et al, 2014; Koch et al, 2016), we hypothesise that BOLD responses associated with target detection are restricted to somatosensory regions, whereas activity in the frontoparietal network reflects cognitive processes that follow from task requirements.…”
Section: Introductionmentioning
confidence: 99%
“…In EEG, the disruption of connectivity between frontal and parietal electrodes at alpha (8–12 Hz) frequencies has been shown to occur in disorders of consciousness (Chennu et al 2014a , b ) and sedation (Chennu et al 2016a , b ). Although it is still debated whether these are signatures of conscious processing or of processes that almost invariably accompany it (Farooqui and Manly 2017 ), brain connectivity patterns currently provide, in practice, useful insights into the transitions between levels of consciousness.…”
Section: Introductionmentioning
confidence: 99%